Dimerization of two alkyne units: model studies, intermediate trapping experiments, and kinetic studies - Fabig, Sven; Haberhauer, Gebhard; Gleiter, Rolf (Journal of the American Chemical Society, 2015)
By means of high level quantum chemical calculations (B2PLYPD and CCSD(T)), the dimerization of alkynes substituted with different groups such as F, Cl, OH, SH, NH2, and CN to the corresponding diradicals and dicarbenes was investigated. We found that in case of monosubstituted alkynes the formation of a bond at the nonsubstituted carbon centers is favored in general. Furthermore, substituents attached to the reacting centers reduce the activation energies and the reaction energies with increasing electronegativity of the substituent (F > OH > NH2, Cl > SH, H, CN). This effect was explained by a stabilizing hyperconjugative interaction between the σ* orbitals of the carbon-substituent bond and the occupied antibonding linear combination of the radical centers. The formation of dicarbenes is only found if strong π donors like NH2 and OH as substituents are attached to the carbene centers. The extension of the model calculations to substituted phenylacetylenes (Ph-C≡C-Y) predicts a similar reactivity of the phenylacetylenes: F > OCH3 > Cl > H. Trapping experiments of the proposed cyclobutadiene intermediates using maleic anhydride as dienophile as well as kinetic studies confirm the calculations. In the case of phenylmethoxyacetylene (Ph-C≡C-OCH3) the good yield of the corresponding cycloaddition product makes this cyclization reaction attractive for a synthetic route to cyclohexadiene derivatives from alkynes.